Cytoreductive surgery and heated intrathoracic chemotherapy for thoracic extension of Pseudomyxoma peritonei. Issue 4 (2016) - Doyle, Mathew P.; Villanueva, Claudia I.; Davies, Samuel; Fermanis, Gary G.; Horton, Matthew D.; Morris, David L.
No abstract available